Application the Cognitive-Behavioral Model of Relapse in Preventing Bipolar Relapse at RSI. Madinah Tulungagung - Agustin Widyowati; Katmini; Predito Prihantoro (Journal Of Nursing Practice, 2024)
Background: Mental health has a low early mortality rate, but contributes the most to disability and recurrence is an indicator of successful treatment of mental disorders, including bipolar. Bipolar relapse is caused by many factors or high-risk situations. Purpose: The purpose of this study was to analyze the determinants of bipolar relapse from a cognitive-behavioral model of relapse. Method: This research was conducted at Islamic Hospital of Madinah Tulungagung used a correlational design with a cross sectional approach to 108 respondents who were taken using a simple random sampling technique. The exogenous variables were genetics, age of onset, gender, occupation, marriage, family support, social capital, stigma, self-efficacy, motivation, medication adherence and the endogenous variable was bipolar relapse, using a questionnaire and analyzed path analysis. Results: Genetics, occupation, social capital, self-efficacy, motivation, medication adherence, community stigma and family support have a direct effect on bipolar relapse with a p-value <0.05. Community stigma has an indirect effect on bipolar relapse through medication adherence with a path coefficient (b) of 11.35. Family support has an indirect effect on bipolar relapse through medication adherence (b = 8.9), motivation (b = 11.89) and self-efficacy (b = 18.26). The most effective way to prevent bipolar relapse is family support which has an indirect effect on bipolar relapse through self-efficacy. Conclusion: Family support is expected to increase self-efficacy so that it is effective in preventing bipolar relapse.